A panel discussion: broadening learning by incorporating industry professionals in education - Cole, J.B.; Mrode, Raphael A.; Olson, K.M.; Knap, P. (Wageningen University & Research, 2022)
Educating future animal breeders and geneticists is fundamentally important. During this training, young scholars, both those completing graduate and post-doctoral studies and those establishing their careers, benefit from understanding the range of professional opportunities available, and the skills they require. This includes exposure to the needs of various livestock sectors. Through a panel discussion in the Education session, industry-based experts engaged in developing nation, extensive, and intensive production systems will share their experiences and discuss opportunities to serve a range of livestock industries. In an interactive session, the moderator will present questions to the panel. This will be followed by an open discussion with the audience delving further into the points raised. The goal of the session is to broaden the attendees? understanding, particularly younger scholars, of the skills needed and professional opportunities available to meet the needs of livestock industries globally in animal breeding and genetics.